Scanning Plat Kendaraan Pada Apill Area Dengan Menerapkan Algoritma Connected Component Labelling - Kiki Hardiyanti (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
Research about vehicle number plate scanning detection system that passes Apill Area (Traffic signaling equipment) using CCTV which will be developed in this study. Detection of the vehicle number plate will use a camera mounted on every corner of the traffic light pole. This detection process is carried out by taking data using the cctv camera, changing the image into a greyscale then holding it to find its binary value. Segmentation of this research uses a connected component labeling algorithm to be used for testing whether the plate is a plate or not. The contribution of this study is to divide the letters and numbers of character regions, to avoid introducing errors especially for characters with similar shapes and structures.